2006
DOI: 10.1111/j.1365-2966.2006.09918.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolving turbulence and magnetic fields in galaxy clusters

Abstract: We discuss, using simple analytical models and MHD simulations, the origin and parameters of turbulence and magnetic fields in galaxy clusters. Three physically distinct regimes can be identified in the evolution of cluster turbulence and magnetic fields. Firstly, the fluctuation dynamo will produce microgauss-strong, random magnetic fields during cluster formation and major mergers. Turbulent velocity of about 300 km/s can be maintained at scales 100-200 kpc. The magnetic field is intermittent, has a smaller … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
320
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 268 publications
(350 citation statements)
references
References 99 publications
(201 reference statements)
29
320
1
Order By: Relevance
“…Subramanian et al 2006;Brunetti & Jones 2014), it can be essential to separate solenoidal from compressive turbulent motions. For example, in recent work Miniati (2015) showed that the cluster-wide ICM compressive turbulence component is likely to have a steep (Burgers-law-like) spectrum, greatly reducing the power available for cosmic ray acceleration compared to a Kraichnan-like spectrum unless that power can cascade to very small scales, where it can more efficiently transfer energy to the cosmic rays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subramanian et al 2006;Brunetti & Jones 2014), it can be essential to separate solenoidal from compressive turbulent motions. For example, in recent work Miniati (2015) showed that the cluster-wide ICM compressive turbulence component is likely to have a steep (Burgers-law-like) spectrum, greatly reducing the power available for cosmic ray acceleration compared to a Kraichnan-like spectrum unless that power can cascade to very small scales, where it can more efficiently transfer energy to the cosmic rays.…”
Section: Introductionmentioning
confidence: 99%
“…The rarefied media in galaxy clusters (ICMs) are highly dynamic and likely to be turbulent, with strong motions on many scales that can significantly influence a wide range of ICM physical processes (e.g., Schekochihin & Cowley 2006;Subramanian et al 2006;Brunetti & Lazarian 2007;Jones et al 2011). These motions may be driven by processes originating on galactic scales (e.g., star burst winds, AGN outflows and bubbles, (e.g., O'Neill et al 2009;Morsony et al 2010;Mendygral et al 2012;Gaspari et al 2012)), possibly ICM-based magneto-thermal instabilities (e.g., Kunz et al 2011;ZuHone et al 2013), but especially by cluster-scale processes associated with cluster formation out of cosmological, large-⋆ Email:franco.vazza@hs.uni-hamburg.de scale structure (e.g., Dolag et al 2005;Vazza et al 2006;Ryu et al 2008;Lau et al 2009;Vazza et al 2011a;ZuHone 2011;Miniati 2014;Schmidt et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A very similar view and approach are used in the recent work by Subramanian et al (2006), in which the magnetic £elds in non-cooling core clusters were also assumed to be maintained by turbulence. In that environment the turbulence is due to merger events and galaxy motion, whereas here it is due to the in¤ation and buoyant motion of radio bubbles.…”
Section: Dynamo Conceptsmentioning
confidence: 98%
“…The origin of these components is still unclear and a subject of lively debate. Potentially these components contribute to the energy of the ICM and drive complex physical processes that may significantly alter our present (simplified) view of the ICM (Schekochihin et al 2005;Subramanian, Shukurov, & Haugen 2006;Brunetti & Lazarian 2011).…”
Section: Galaxy Clusters and Large-scale Structurementioning
confidence: 99%